The Relation of Interpersonal Communication and Sibling Support on Social Interactions of Autistic Children - Ni Luh Putu Yunianti Suntari; I Dewa Ayu Ketut Surinati; Ni Nyoman Hartati (Nursing and Health Sciences Journal (NHSJ), 2022)
Autism is a serious developmental disorder, its impact on certain nervous systems causing certain difficulties commonly affect one’s difficulty with communication and social interaction. Interpersonal communication and sibling support need to be observed in the development of children with autism This study examined the relation between interpersonal communication and sibling support on social interaction of children with autism. We drew data with a sample population of 32 children on the autism spectrum. We use cross sectional approach to study it’s correlation. Our result found that interpersonal relations (X1) correlate to social interaction (Y) with a r-score of 0.764 which can be concluded that there was a positive correlation between interpersonal communication and social interaction. We also found that sibling support (X2) correlation to social interaction with a r-score of 0.284 which is lesser than r-table of 0.349, meaning that there was no correlation between sibling support to social interaction of children with autism. Finding underscore the crucial problem of children with autism was their difficulties on social interactions. Interpersonal communication and siblings support that they had doesn’t always translate to the development of social skill in children with autism. Parent involvement was an important aspect on the development of social skills.